Characteristics of spawners of chum salmon Oncorhynchus keta from commercial stock of Iturup Island - A. N. Elnikov; O. V. Zelennikov (Известия ТИНРО, 2023)
Chum salmon spawners returned for spawning in the rivers of Prostor and Kurilsky Bays on Iturup Island (Kuril Islands, Sakhalin Region) were examined in the period from September 19 to November 4, 2022. Both females and males had mostly the age 3+ (68.8 % in the Prostor Bay and 62.2 % in the Kurilsky Bay). The portion of males in the age 2+ was in 3.8 times higher than the portion of females, with the average value of 19.2 %; the summary portion of older age groups (4+ and 5+) was 15.4 %. Chum salmon spawners were distinguished by relatively small body weight, similar for the fish of the same age in both bays, on average 2.27 and 2.57 kg for females and males of age 3+, respectively, that was lower than the weight of chum salmon spawners in the previous 8 years.